2017
DOI: 10.1016/j.scr.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intracerebroventricular injections of human umbilical cord mesenchymal stem cells delay motor neurons loss but not disease progression of SOD1G93A mice

Abstract: Stem cell therapy is considered a promising approach in the treatment of amyotrophic lateral sclerosis (ALS) and mesenchymal stem cells (MSCs) seem to be the most effective in ALS animal models. The umbilical cord (UC) is a source of highly proliferating fetal MSCs, more easily collectable than other MSCs. Recently we demonstrated that human (h) UC-MSCs, double labeled with fluorescent nanoparticles and Hoechst-33258 and transplanted intracerebroventricularly (ICV) into SOD1G93A transgenic mice, partially migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
3
27
0
2
Order By: Relevance
“…Human umbilical cord (huc) is a suitable source of mesenchymal stem cells (MSCs) which secrete a variety of trophic factors and cytokines as well as show strong anti-inflammatory and immunomodulatory capacities [6]. A study has verified that PE accelerates neuroglial marker expression in umbilical cord Wharton's jelly-derived MSCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Human umbilical cord (huc) is a suitable source of mesenchymal stem cells (MSCs) which secrete a variety of trophic factors and cytokines as well as show strong anti-inflammatory and immunomodulatory capacities [6]. A study has verified that PE accelerates neuroglial marker expression in umbilical cord Wharton's jelly-derived MSCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects may be mediated by the activation of the p-Akt survival pathway in motor neurons and astrocytes. However, UC-MSC administration did not prevent muscle denervation and disease progression in SOD1 G93A mice [57].…”
Section: Msc Application In Als Rodent Modelsmentioning
confidence: 99%
“…Indeed, NSCs can also elicit protection or regeneration of perilesional tissues and circuitries [31,33]. In the past ten years, several preclinical studies focusing on the use of stem cells in ALS transgenic animal models have shown promising results [26,27,31,[34][35][36][37]. Furthermore, Teng and colleagues demonstrated an increased therapeutic effect when performing multiple dose-escalating injections in different CNS sites, indicating the importance of administering enough cells into critically functional areas to hinder ALS-induced damage [31].…”
Section: Neural Stem Cells and Motor Neuron Diseases: Cell Transplantmentioning
confidence: 99%
“…Currently, despite extensive research efforts, no successful treatment for MNDs is available. Nonetheless, preclinical studies on stem cell-based transplantation therapy have yielded significant and interesting results, showing neuroprotective effects, improved functional outcomes, and delayed progression in treated groups [26,27,31,[34][35][36][37]. The main limitation of this approach in regard to clinical translatability is the low engraftment success and the high rate of stem cell death following transplantation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%